Axon Branch-Specific Semaphorin-1a Signaling in Drosophila Mushroom Body Development - Zwarts, Liesbeth; Goossens, Tim; Clements, Jason; Kang, Yuan Y.; Callaerts, Patrick (Frontiers in Cellular Neuroscience, 2016)
Correct wiring of the mushroom body neuropil in the Drosophila brain involves appropriate positioning of different axonal lobes, as well as the sister branches that develop from individual axons. This positioning requires the integration of various guidance cues provided by different cell types, which help the axons find their final positions within the neuropil. Semaphorins are well known for their conserved roles in neuronal development and axon guidance. We investigated the role of Sema-1a in mushroom body (MB) development more closely. We show that Sema-1a is expressed in the MBs as well as surrounding structures, including the glial transient interhemispheric fibrous ring (TIFR), throughout development. By loss- and gain-of-function experiments, we show that the MB axons display lobe and sister branch-specific Sema-1a signaling, which controls different aspects of axon outgrowth and guidance. Furthermore, we demonstrate that these effects are modulated by the integration of MB intrinsic and extrinsic Sema-1a signaling pathways involving PlexA and PlexB. Finally, we also show a role for neuronal- glial interaction in Sema-1a dependent β-lobe outgrowth.